STRUKTUR, TATA RUANG DAN ESTETIKA PALINGGIH PADMASANA SMP NEGERI 2 SINGARAJA KECAMATAN BULELENG (PERSPEKTIF SOSIAL RELIGIUS) - Made Sudiartana; I Made Suweta; I Made Ariasa Giri (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2022)
The construction of Palinggih Padmasana as a simbul (Niyasa) that embodies Ida Sang Hyang Widhi needs to pay attention to the structure, layout, and aesthetics of Palinggih, because it is related to the sanctity of Palinggih itself as the ancestral heritage of Hindus.  Based on the problems studied, the type of research used in this study is descriptive - qualitative research because it is a type of case study, namely research that only describes, describes, and summarizes all the objects studied from various existing conditions and situations. The research was located at SMPN 2 Singaraja, Buleleng District, Buleleng Regency. The results of the study were processed as follows (1) The Structure and Layout of Padmasana's Most Powerful Room in The Junior High School (SMP) Negeri 2 Singaraja, Buleleng District, applies the tri Hita Karana concept in its construction, also guided by the concept of the tri mandala zone. (2) Padmasana's Most Intense Aesthetic Value in The Junior High School (SMP) Negeri 2 Singaraja Buleleng District is adjusted to three characteristics, namely Unity, Complexity and Solemnity. (3) Social Religious Perspectives of Residents in Junior High School (SMP) Negeri 2 Singaraja, Buleleng District, on the Structure, Spatial And Aesthetics of Padmasana. Most powerfully Padmasana which is the place of worship of Hyang Widhi which is full of religious values has contributed to the formation of the religious character of the school residents because of the intense relationship between the school residents and god, with their neighbors and with their environment, or often known as Tri Hita Karana.Keywords: Structure, Layout, Aesthetics, Padmasana, Social Religious